-16p-5(3-4p)=2(p-4)-11

Simple and best practice solution for -16p-5(3-4p)=2(p-4)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16p-5(3-4p)=2(p-4)-11 equation:


Simplifying
-16p + -5(3 + -4p) = 2(p + -4) + -11
-16p + (3 * -5 + -4p * -5) = 2(p + -4) + -11
-16p + (-15 + 20p) = 2(p + -4) + -11

Reorder the terms:
-15 + -16p + 20p = 2(p + -4) + -11

Combine like terms: -16p + 20p = 4p
-15 + 4p = 2(p + -4) + -11

Reorder the terms:
-15 + 4p = 2(-4 + p) + -11
-15 + 4p = (-4 * 2 + p * 2) + -11
-15 + 4p = (-8 + 2p) + -11

Reorder the terms:
-15 + 4p = -8 + -11 + 2p

Combine like terms: -8 + -11 = -19
-15 + 4p = -19 + 2p

Solving
-15 + 4p = -19 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
-15 + 4p + -2p = -19 + 2p + -2p

Combine like terms: 4p + -2p = 2p
-15 + 2p = -19 + 2p + -2p

Combine like terms: 2p + -2p = 0
-15 + 2p = -19 + 0
-15 + 2p = -19

Add '15' to each side of the equation.
-15 + 15 + 2p = -19 + 15

Combine like terms: -15 + 15 = 0
0 + 2p = -19 + 15
2p = -19 + 15

Combine like terms: -19 + 15 = -4
2p = -4

Divide each side by '2'.
p = -2

Simplifying
p = -2

See similar equations:

| 4y^2-24y+20= | | 4y^2-12y-40= | | 3(-3y-3)=-9y+23 | | 11+8x=23 | | 3[4-(-2x-5)]=48x+132 | | 16t^2-140t=68 | | 10+x+14=30+5 | | 16t^2-12ft-182=0 | | 7b= | | -8x-3=4x+9 | | a+4b= | | 2x-8+7= | | 6a+9b= | | 7.3x-3.1=11.5 | | 5t^2-15+2=10 | | 8a+3b= | | X^2+2x=60 | | 7x+5(x+2)+4= | | 3p+5=30p | | 4(logx-1)=18 | | 16x^4+16x^2+3=0 | | 12a+15b= | | (7x-4)(7x+5)= | | 3v+w+8-2v+2= | | -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 | | 8(4x+4)= | | -6(x+3)+2x+6=8x+7 | | 20*7-4*7= | | -16t^2+144t-160=0 | | 15w+21=3(5w-7) |

Equations solver categories